Evaluation of critical factors in the preparation of saliva sample from healthy subjects for metabolomics - Nam, Miso; Jo, Sae rom; Park, Jae Ho; Kim, Min-Sun (Journal of pharmaceutical and biomedical analysis, 2023)
Saliva has been the subject of an increasing number of clinical metabolomics investigations, and salivary metabolic profiling has suggested potential diagnostic biomarkers for several human diseases, contributing to a better understanding of their mechanisms. However, a comprehensive evaluation of factors that may influence salivary metabolic profiling is still lacking. In the present study, we examined the effects of solvent, collection method, and storage stability on salivary metabolic profiles using ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry. A total of 51 metabolites were identified in saliva samples and assessed by principal component analysis and univariate tests. Acetonitrile was a more effective organic solvent for removing large molecules from saliva samples than methanol. A comparison of the salivary metabolite profile of unstimulated and stimulated saliva revealed variations in the levels of 15 metabolites, which are organic acids, purine metabolites, choline and its metabolites, taurine, and N-acetylcadaverine. After saliva collection, room temperature storage induced increases in most amino acids and decreases in the other metabolites within 24 h. These changes were less pronounced after storage at 4 °C. No distinct changes in metabolite levels were observed over 30 days at − 20 °C, except for adenosine, inosine, and guanosine. This approach can be applied to understand the diversity and stability of salivary metabolic profiles and investigate precise disease biomarkers. •Method for salivary metabolic profiling using LC-MS/MS was optimized.•Acetonitrile removed large molecules from saliva more effectively than methanol.•Saliva collection method influenced salivary metabolite profiling.•Purine metabolite levels changed significantly during long-term storage of saliva.